Does state ownership really matter for capital structure in selected G-20 economies?* - Amin, Muhammad Yusuf; Besim, Mustafa; Ul Haq, Zahoor (Routledge Journals, Taylor & Francis Ltd, 2019)
The effect of state ownership on the capital structure decisions of enterprises in selected G-20 countries is estimated using financial and accounting data of 252 state-owned and 6503 non-state-owned firms for the period 2011-2015. The results indicate that state ownership is positively associated with leverage in all the selected G-20 countries. However, this phenomenon changed when countries were considered according to their income levels because state-owned enterprises in high-income countries carry more debt, while the opposite is true for lower-middle-income countries. The results were also divergent when the effects of various firm-specific variables were compared between state and non-state-owned enterprises across the development spectrum.
Keywords: State-owned enterprises; income level; capital structure; tangibility; size; tobin's Q; profitability